An overview of vine water status assessment - Salgado-Pirata Madalena; Marques da Silva José Rafael (Ciência e Técnica Vitivinícola)
In regions influenced by the Mediterranean climate, the distribution of rainfall is uneven throughout the year, with rainfall concentrated in winter and hot, dry summers, which is being boosted by climate change towards a worsening of this situation. Due to the high socioeconomic relevance of viticulture in these regions, monitoring the vine water status is extremely important. Although vineyards are typically a rainfed crop, water stress can result in quantitative and qualitative production losses, and irreversible damage to plants. The complexity of grapevine’s physiological response to water availability can be measured through indicators, which quantify the degree of stress the plants are under, and thus decisions can be made on this basis. Therefore, this work describes the main water stress indicators used in viticulture, as well as the particularities of each one and the relationship between them, contributing to a better understanding.